Research on Introduction to Famous Works and Cultivation of Humanistic Quality in the Teaching of British and American Literature Based on Network Information. Issue 3 (February 2021) - Cheng, Tingli; Deng, Min
Abstract: Classics reading can significantly improve our cultural literacy, It is the main content of British and American literature teaching in the classroom. But due to some teaching ideas, many universities in the process of curriculum and teaching practice rejection of British and American literature teaching content. Now few people can calm down and deep reading, the reading atmosphere also gradually lost humanities, this article expounds the defects of traditional British and American literature teaching mode, and how to overcome these disadvantages, looking for solutions, innovative ideas and make full use of big data under the environment of network resources for classics reading, to cultivate people's humanistic quality.